Pengaruh Model Quantum Teaching Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS Kelas IV SDN Sidotopo 1 Surabaya - Ramadhan, Muhamad Zakhi; Siswoyo, Andika Adinanda (Indo-MathEdu Intellectuals Journal, 2025)
This research was motivated by the low learning outcomes in the IPAS subject, particularly on the topic of force, among fourth-grade students at SDN Sidotopo 1 Surabaya. The aim of this study was to determine the effect of the quantum teaching learning model on students’ learning outcomes in the topic of magnetic force. This research employed a quantitative approach with a quasi-experimental design, specifically using the nonequivalent control group design. The sampling technique used was saturated sampling. The population of the study consisted of 60 students from classes IVA and IVB. Data collection methods included observation and testing. Data were analyzed descriptively quantitatively. Based on the results of the mann-whitney hypothesis test at a 5% significance level, the p-value obtained was 0.008. Since 0.008 < 0.05, the null hypothesis H₀ was rejected and the alternative hypothesis H₁ was accepted. The results of the study indicate that the quantum teaching learning model has a significant effect on students learning outcomes in the topic of magnetic force.